Multimodal residual stress evaluation following one-sided dimpling in a Ti-6Al-4V alloy plate (Fracture and Structural Integrity, 2026)
Residual stress significantly influences the mechanical performance, fatigue resistance, and structural reliability of titanium alloys used in engineering applications. This study investigates the residual stress distribution induced by one-sided dimpling in Ti-6Al-4V alloy using a combined experimental–numerical approach. Localized plastic deformation produced by spherical indentation generates stress fields that are difficult to characterize with a single technique. Residual stresses in the plane were evaluated using Focused Ion Beam–Digital Image Correlation (FIB-DIC) and Electronic Speckle Pattern Interferometry (ESPI). To evaluate the residual stress through the sample thickness, the cross-section warp method was used, that analyze the warping (deplanation) of the cross-section after cutting and provides an alternative way to infer the internal stress distributions and complements existing measurement techniques. The results reveal compressive residual stresses near the dimpled surface and tensile stresses developing at greater depths due to elastic recovery and equilibrium constraints. Finite element simulations match the experimentally observed stress distributions and confirm the reliability of the proposed methodology. The validated finite element model provides a predictive framework for future studies, enabling systematic analysis of how indentation depth and the indenter diameter affect the magnitude and distribution of compressive residual stresses, and supporting the optimization of dimpling parameters for improved structural performance.
Keywords: Residual stress; One-sided Dimpling; Focused Ion Beam – Digital Image Correlation (FIB-DIC); Electronic Speckle Pattern Interferometry (ESPI); , Finite Element Method (FEM)